Comparative Analysis of Millennial and Generation Z Perceptions of the Use of Islamic Banking Products - Wasilatur Rohmah; Zaid Raya Argantara (Penerbit Hellow Pustaka, 2026)
Sharia banking is growing and becoming a choice for people seeking financial alternatives that comply with Sharia principles. However, differences in understanding and using Sharia banking products are a significant concern. Millennials and Generation Z have different characteristics and preferences in accessing financial services, making it important to understand how these two generations perceive Sharia banking products. The research questions are: 1. What are the perceptions of millennials and Generation Z regarding the use of Sharia banking products? 2. What factors influence the interest of millennials and Generation Z in using Sharia banking products? The method used in this study was qualitative, with data collection using interviews, observations, and documentation. The analysis technique used by Miles and Huberman included data reduction, data presentation, and conclusion drawing. For data testing, the study utilized source triangulation. The research results show that millennials and Generation Z have very positive views on Islamic banking, despite differences in their approaches. Millennials place greater emphasis on practicality and efficiency, while Generation Z values ​​technological innovation and the application of Islamic principles. Social factors, easy access to digital technology, and attractive promotions are key factors driving their interest. This research also highlights the importance of Islamic financial literacy, the development of digital innovation, and strengthening marketing strategies by Islamic banks to meet the needs of the younger generation. Therefore, Islamic banking products have a significant opportunity to attract the attention of millennials and Generation Z if the services offered are tailored to their preferences.